Transformation of the ukrainian peasantry under the conditions of stalinism: modernization or adaptation? - Prysiazhniuk Yuriі (Ukrainian Peasant, 2025)
The aim of the article is to explore the complex processes of the destruction of traditional Ukrainian peasantry by the Stalinist (more broadly, Bolshevik) regime during the period of «socialism building», while also focusing on the mental aspects that enable an integrated understanding of these historical phenomena and their modifications. The scientific novelty of the research lies in its innovative approach to studying the modern transformation of traditional Ukrainian peasantry, providing an exclusive analysis. The author substantiates, deepens, and in some cases, discusses and challenges the claims, hypotheses, and assumptions identified in contemporary historiography. In general, considering the nature of modernization processes, the destruction of the peasantry by the totalitarian regime turned out to be «quite effective» in the demographic, social, and economic spheres. However, on a mental level, history proved «wiser», preserving a part of the traditional peasant world. Methodological Framework. The study is based on an interdisciplinary approach, as commonly used in the humanities. Specifically, it involves a comprehensive (within the framework of synthesizing several disciplines) investigation of complex social phenomena represented by the terms «culture», «mentality», «society» and others. Also relevant are the methods of the Receptive Aesthetics concept (reception theory), which emphasizes the active role of engaged readers (primarily professional historians) in interpreting the propositions and generalizations of the proposed narratives. Conclusions. The results of prolonged discussions surrounding the transformation of the traditional peasant world under the influence of modernization processes fall into two broad perspectives: first, «the demise of the village is a fact», and second, «peasantry is still with us today». The need for further discussions and scientific inquiries, as well as the emergence of new knowledge, is evident. The creation of new syntheses lies in the improvement of interdisciplinary approaches, integrating the potential of both the humanities and natural sciences, as well as developing new thematic directions. Today, most Ukrainian historians maintain that the sociocultural approach remains effective for further research into the history of the peasantry. However, it should not be regarded as an immutable canon, which is confirmed by some recent developments, particularly in the field of global historiography.